Vehicular fender liner and manufacturing method of the same

A core-sheath composite fiber-based fender liner with a water-repellent film addresses chipping and ice removal issues, offering enhanced sound absorption and ease of manufacturing.

JP2025013229APending Publication Date: 2025-01-24HIROTANI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024107026
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-13
Filing Date
2024-07-02
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing vehicle fender liners made of nonwoven fabric lack sufficient chipping resistance and ice removal properties, with water penetration leading to ice growth and difficulty in peeling off, and require complex adhesion processes in resin-based solutions.

Method used

A fender liner composed of a two-layer structure formed from a core-sheath composite fiber, where the sheath is melted and solidified to create a water-repellent film on a base material, eliminating the need for adhesion and enhancing chipping resistance and ice removal.

Benefits of technology

The solution provides excellent sound absorption, chipping resistance, and ice removal properties while ensuring easy formation into three-dimensional shapes, with improved productivity and reduced water absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013229000001_ABST
    Figure 2025013229000001_ABST
Patent Text Reader

Abstract

To provide a vehicular fender liner that has excellent sound absorbency and is superb in chipping withstanding and ice peeling capabilities.SOLUTION: A film material is formed on a first stage by fusing and solidifying one surface of a sheath material of a core-sheath type composite fiber. Thereafter, the core-sheath type composite fiber with a film is made flexible, the sheath part is fused and solidified, and a core part is joined. Thus, both an unwoven cloth and film to be made into a base are formed with one core-sheath type composite fiber.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vehicle fender liner that is attached to the inner surface of a wheel house of a vehicle body and has durability (chipping resistance) against collisions with foreign objects such as pebbles kicked up while the vehicle is traveling, and which easily removes adhering ice, and a method for manufacturing the same. [Background technology]

[0002] Generally, a fender liner for a vehicle is known that includes a nonwoven fabric in which a large number of mixed fibers are entangled with each other (Patent Document 1). In this way, a fender liner formed from a nonwoven fabric has impact resistance and soundproofing properties (particularly sound absorption properties) because the countless gaps formed between the entangled fibers absorb the impact caused by the collision of a foreign object. However, chipping resistance against pebbles and the like is insufficient, and water that adheres to the fender liner penetrates into the interior. Therefore, there is also the problem that when the water freezes, ice grows inside and becomes difficult to remove.

[0003] Also known is a fender liner that includes a base layer made of a fiber web in which main fibers and binder fibers are entangled, and a water-resistant protective film made of LDPE resin that is integrally bonded to the base layer (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-112661 A [Patent Document 2] JP 2011-240821 A Summary of the Invention [Problem to be solved by the invention]

[0005] The product shown in Patent Document 1 is superior to resin molded products in terms of impact resistance and soundproofing, but has the problem of being inferior to resin molded products in terms of chipping resistance and ice adhesion / peeling properties.

[0006] The one shown in Patent Document 2 has a water-resistant protective film adhered to the base layer, and thus has superior chipping resistance compared to the one shown in Patent Document 1.

[0007] However, the method shown in Patent Document 2 involves coating the surface of a fiber web with a molten resin made of LDPE, pressing with a roller to form a laminated sheet in which a water-resistant protective film made of LDPE resin is adhered to a base layer, and then hot-molding the laminated sheet to form a vehicle fender liner, which has problems such as the need for a bonding process for joining. When hot-press molding is performed to mold a laminate of the base material and the water-resistant protective film into a desired three-dimensional shape, the heat from the press molding melts the binder fibers of the base layer and at the same time melts the water-resistant protective film, thereby fusing it to the base layer, so it is necessary to control the heating temperature so that it does not become too high so that the water-resistant protective film is not melted and destroyed.

[0008] In view of the above problems, an object of the present invention is to provide a vehicle fender liner that has excellent sound absorbing properties as well as excellent chipping resistance and ice removal properties, and a manufacturing method thereof. [Means for solving the problem]

[0009] The present invention is characterized in that, instead of laminating another membrane material on a substrate made of a nonwoven fabric, a two-layer structure consisting of a substrate layer and a membrane layer is realized by forming a membrane material from the substrate nonwoven fabric itself.Furthermore, instead of preparing two types of fiber materials as the base nonwoven fabric of the substrate layer and the binder fiber that bonds the nonwoven fabrics together, the core-sheath type composite fiber that is often used as the binder fiber itself is used as the base material and binder fiber, so that only one type of nonwoven fabric is sufficient.

[0010] Specifically, one surface of the sheath material of the core-sheath composite fiber is melted and solidified in the first stage to form a membrane material, and then the membrane-attached core-sheath composite fiber is softened and the sheath portion is melted and solidified to join the core portion, thereby forming both the base nonwoven fabric and the membrane from a single core-sheath composite fiber.

[0011] The invention of claim 1 is characterized in that the substrate is a sheath-core composite fiber in which both the core and sheath are made of PET fiber, the sheath portion is melted and solidified to bond the core portion, and the substrate is made of a fiber web formed by bonding the core portion together, the sheath-core composite fiber accounts for 50% by weight to 95% by weight of the total weight, and the water-repellent fiber made of PET fiber accounts for 5% by weight to 50% by weight, the water-repellent fiber is dispersed and mixed into the sheath portion of the sheath-core composite fiber, one surface of the fiber web is provided with a generated film that is high-density and breathable by melting and solidifying the sheath portion, and the layer other than the generated film is a main layer that is lower in density than the generated film, the film thickness of the generated film is thinner than the thickness of the main layer, the water-repellent fiber is dispersed and mixed into the melted and solidified sheath portions of both the generated film and the main layer, and the main layer is formed into a fender liner shape so that the main layer is on the tire house side and the generated film is the outermost surface on the tire side.

[0012] The invention of claim 2 is characterized in that, in the vehicle fender liner described in claim 1, a portion of the water-repellent fibers are replaced with mixed fibers made of PET fibers so that at least 5% by weight of the water-repellent fibers remain.

[0013] The invention of claim 3 is the vehicle fender liner of claim 1, wherein the produced film has an average dynamic friction coefficient of 0.3 or less, a thickness of 0.05 mm to 2.0 mm, and a basis weight of 50 g / m 2 ~300g / m 2 The total thickness including the produced film is 1.0 mm to 15 mm, and the basis weight is 400 g / m 2 ~1600g / m 2 It is characterized by a chipping load resistance of 150 kg or more and an ice peeling load of 30 N or less.

[0014] The invention of claim 4 is the vehicle fender liner according to claim 2, wherein the produced film has an average dynamic friction coefficient of 0.3 or less, a thickness of 0.05 mm to 2.0 mm, and a basis weight of 50 g / m 2 ~300g / m 2 The total thickness including the produced film is 1.0 mm to 15 mm, and the basis weight is 400 g / m 2 ~1600g / m 2 It is characterized by a chipping load resistance of 150 kg or more and an ice peeling load of 30 N or less.

[0015] The invention of claim 5 is a vehicle fender liner according to any one of claims 1 to 4, characterized in that the core portion of the sheath-core composite fiber is a PET fiber having a fineness of 1.5 dtex to 15 dtex, a fiber length of 10 mm to 100 mm, and a melting point of 220°C to 270°C that is 30°C or more higher than the melting point of the sheath portion, and the sheath portion has a fineness of 1.5 dtex to 15 dtex, a fiber length of 10 mm to 100 mm, and a melting point of 90°C to 180°C.

[0016] The invention of claim 6 is the vehicle fender liner of claim 5, wherein the water-repellent fiber is a PET fiber having a fineness of 1.5 dtex to 15 dtex, a fiber length of 10 mm to 100 mm, and a melting point of 220°C to 270°C.

[0017] The invention of claim 7 is the vehicle fender liner according to claim 6, characterized in that the tensile strength is 90N or more, the tear strength is 80N or more, and the bending strength is 1.5N or more.

[0018] The invention of claim 8 is a method for manufacturing a vehicle fender liner according to any one of claims 1 to 4, comprising the steps of: discharging fibers containing a core-sheath type composite fiber and a water-repellent fiber by an air-laying method to form a sheet-like base material made of a fibrous body; or entangling the fibers by a spreader, a fleece machine, or a carding machine to form a sheet-like base material made of a fibrous body; heating one surface of the base material at 180°C to 240°C; and pressing and holding the base material at a predetermined thickness for 0.5 to 30 seconds to form a sheet-like base material on one surface of the base material having an average dynamic friction coefficient of 0.3 or less, a thickness of 0.05 mm to 2.0 mm, and a basis weight of 50 g / m 2 ~300g / m 2 The substrate on which the produced film is formed is heated in a heating furnace at 120°C to 240°C for 10 seconds to 60 seconds to facilitate molding of the substrate in the state in which the produced film is formed, and the heated substrate is compression molded while being cooled in a press mold having a shape of a vehicle fender liner, so that the produced film is disposed on the tire side, and the overall thickness including the produced film is 1 mm to 15 mm and the basis weight is 400 g / m 2 ~1600g / m 2 The present invention is characterized in that the vehicle fender liner is formed by molding the above-mentioned.

[0019] The invention of claim 9 is characterized in that, in the manufacturing method for a vehicle fender liner as described in claim 8, the specified thickness when one surface of the base material is heated and compressed is 5 to 100 times the thickness before compression, and after the generated film is formed, the thickness is restored to 1.0 to 0.6 times the thickness before compression, and then the entire product is heated and compression molded while being cooled in a press mold having a shape of the vehicle fender liner, to form the vehicle fender liner. Effect of the Invention

[0020] According to the present invention, it is possible to achieve high sound absorbing performance, excellent chipping resistance and excellent ice peeling properties. At the same time, it can be easily molded into a three-dimensional shape. In particular, the core-sheath type composite fiber is used as the base material, and one side of the fiber is heated and pressurized to melt the sheath fiber to form the resulting film, so there is no need for adhesion, which is necessary in conventional types consisting of a base nonwoven fabric and a film, and productivity is excellent. The resulting film has a small friction coefficient and is slippery, so it has excellent chipping resistance. In addition, by including water-repellent fibers in the main body layer, it is possible to suppress water absorption from the tire house side, and by including water-repellent fibers in the resulting film, it has excellent ice peeling properties from the tire side. [Brief description of the drawings]

[0021] [Figure 1] 1 is a side view of a main portion showing the front part of a vehicle to which a fender liner according to a first embodiment of the present invention is attached. [Diagram 2] FIG. 2 is an enlarged cross-sectional view taken along line AA in FIG. 1, showing the fender liner and its surrounding area. [Diagram 3] FIG. 3 is a partially enlarged view of the fender liner in FIG. 2. [Figure 4] FIG. 4 is a table showing the blending ratio of each fiber for the examples of the present invention and the comparative examples. [Diagram 5] FIG. 5 is a table comparing various performances of the examples of the present invention and the comparative examples. [Figure 6] FIG. 6 is a photomicrograph at 50x showing a cross section of Example 3. [Figure 7A] FIG. 7A is a graph comparing the average dynamic friction coefficients of Example 8 and Comparative Example 3. [Figure 7B] FIG. 7B is a graph comparing the average dynamic friction coefficients of Example 9 and Comparative Example 3. [Figure 8] FIG. 8 is a diagram showing the results of measuring the normal sound absorption coefficient of Examples 1, 3 and 6 from the produced film side. [Figure 9] FIG. 9 is a table showing the types and blending ratios of each fiber of Examples 11 to 25, various performances, and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, in which: It should be noted that the following description of the preferred embodiments is merely exemplary in nature.

[0023] (Embodiment) Fig. 1 is a side view of a main portion showing the front part of a vehicle to which a fender liner according to a first embodiment of the present invention is attached, Fig. 2 is an enlarged cross-sectional view taken along line AA in Fig. 1, showing the fender liner and its surrounding area, and Fig. 3 is a partially enlarged view of the fender liner.

[0024] A vehicle 1 is usually provided with tires 2 on the left and right sides of the front and the left and right sides of the rear, and wheel houses 3 are provided above these tires 2. The wheel houses 3 are also called wheel house panels or wheel housings, and constitute a part of the vehicle body. The wheel houses 3 are made of metal and are formed into a shape that covers the upper part of the tires 2. The surface of the wheel house 3 facing the tire 2 is the outer surface of the vehicle, and a fender liner 10 is attached to the wheel house 3 so as to cover this outer surface. The fender liner 10 is an exterior part of the vehicle 1 that prevents the body panel from being damaged by pebbles, muddy water, etc. that the tire 2 splashes up from the road surface while the vehicle 1 is traveling, and reduces noise such as road noise generated by the tire 2 and the road surface.

[0025] Recently, it has become known to omit the wheelhouse 3 and have the fender liner 10 function as a partition between the inside of the vehicle body, such as the engine compartment, and the tire side. In this embodiment 1, an example is described in which the fender liner 10 is provided on the outside of the wheelhouse 3, but this embodiment can also be applied to the case in which the wheelhouse 3 is omitted.

[0026] As shown in FIGS. 1 and 2, the fender liner 10 is molded into a shape that fits the wheel house 3, and is attached to the wheel house 3 with fasteners or the like (not shown).

[0027] Next, an outline of the fender liner 10 of the first embodiment will be described with reference to Figure 3. Note that Figure 3 shows an exaggerated cross section of part of the fender liner for easier understanding. The fender liner 10 is made of a fiber web (substrate) 11 in which water-repellent fibers 18 (and further mixed fibers) are dispersed in core-sheath type composite fibers 17. The substrate 11 has a high-density generated film 15 on the tire 2 side, and is integrally provided with a low-density main body layer 13 on the wheelhouse 3 side. A gap t is provided between the main body layer 13 of the substrate 11 and the wheelhouse 3.

[0028] As shown in Figure 3, the base material 11 is formed by melting the sheath portion of a core-sheath composite fiber 17 to bond the core portion, dispersing water-repellent fibers 18 in the melted and solidified sheath portion, and in some cases further dispersing and bonding mixed fibers, and is integrally provided with a main body layer 13 and a generated film 15.

[0029] The resulting membrane 15 is formed into a high-density membrane by heating and pressurizing one surface of the fiber web 11, which has a structure in which water-repellent fibers 18 are dispersed among core-sheath type composite fibers 17 and, in some cases, mixed fibers are further dispersed and entangled.

[0030] On the other hand, the low-density main layer 13 is a fiber layer formed by heating the entire fiber web 11 on which the above-mentioned generated film 15 is formed to make it in a state that is easy to mold, and then cold molding it in a molding die (not shown) for the fender liner 10, whereby in the areas where the generated film 15 is not formed, the sheath portion of the core-sheath composite fiber 17 melts and solidifies, and the core portion is bonded.

[0031] The main layer 13 and the generated film 15 of the substrate 11 are nonwoven fabrics made of the same material, and after molding, there are some parts where the boundary between the main layer 13 and the generated film 15 is not clear, but in order to clarify the difference between the main layer 13 and the generated film 15, in this embodiment, the high-density layer formed when one side of the substrate 11 is heated and pressed is referred to as the generated film 15, and the other low-density layer is referred to as the main layer 13. In particular, the generated film 15 mainly serves to improve chipping resistance and ice adhesion and peeling properties, and the main layer 13 mainly serves to enhance sound absorption properties.

[0032] Furthermore, while it goes without saying that the inclusion of the water-repellent fibers 18 in the main body layer 13 has the effect of suppressing water absorption from the tire house side, the inclusion of the water-repellent fibers 18 in the produced film 15 has resulted in excellent ice removal properties from the tire side. This result is believed to be due to the produced film 15, which contains the water-repellent fibers 18, exerting anti-icing and anti-water absorption functions, which in turn results in excellent ice removal properties.

[0033] (Sheath-core composite fiber) This is a typical core-sheath type composite fiber, and a detailed description will be omitted here. This core-sheath type composite fiber uses PET (polyethylene phthalate) fibers for both the core and sheath.

[0034] The fineness of the core-sheath type composite fiber is preferably 1.5 dtex to 15 dtex, particularly 3.0 dtex to 8.0 dtex, because a low fineness makes it difficult to handle and reduces productivity, while a high fineness makes the fiber itself thicker, reducing the air resistance and worsening the sound absorption properties.

[0035] The fiber length of the sheath-core composite fiber is preferably in the range of 10 mm to 100 mm, particularly 20 mm to 80 mm, in order to improve processing stability in the manufacturing process of the fender liner. Furthermore, it is preferable to configure the fiber so as to have mechanical crimping, etc., so that a larger number of minute cells can be formed.

[0036] The melting point of the sheath part of the core-sheath type composite fiber is preferably 90°C to 180°C. In particular, if the melting point of the sheath part is too high, the fluidity is insufficient when heated and press molded, and the resulting film cannot follow the molding direction of the substrate layer, resulting in poor moldability. Conversely, if the melting point is too low, there is an increased possibility that the core melts too much and large holes are formed in the substrate. Therefore, the melting point is preferably 90°C to 180°C. On the other hand, the core part needs to have a melting point that does not melt when heated, and is preferably 30°C or more higher than the melting point of the sheath part. Specifically, for example, the core part is preferably a PET fiber with a melting point of 220°C to 270°C.

[0037] In this embodiment, the cores of the sheath-core composite fibers are entangled with each other and the sheaths are melted and hardened to join the cores, so that the fender liner can be easily and reliably molded into a three-dimensional shape and can reliably maintain that shape. Furthermore, the cores of the sheath-core composite fibers exist as entangled fibers that make up the main layer, retaining their fiber shape while being strongly joined by the sheath fibers, which greatly helps to form more micro cells inside the main layer. As a result, a structure (approximately mesh-like structure) that is configured to enhance the sound absorption performance of the main layer can be easily formed.

[0038] (Water-repellent fiber) The water-repellent fibers are PET fibers whose surfaces have been treated with water-repellent agents such as fluorine-based or silicone-based agents. The water-repellent fibers are arranged so as to be intertwined with the core-sheath composite fibers, and are bonded to the sheath when the sheath of the core-sheath composite fibers melts and solidifies. The water-repellent fibers are distributed throughout the substrate, so that they are mixed in both the generated film and the main layer.

[0039] The inclusion of water-repellent fibers makes it possible to suppress the penetration of moisture from the surroundings. Not only that, but the inclusion of water-repellent fibers in the resulting film significantly improved the ice-removal properties. This is thought to be because the inclusion of water-repellent fibers in the resulting film reduces adhesion of moisture, and even if moisture does adhere, it peels off immediately. In addition, the resulting film has a low average dynamic friction coefficient and a smooth surface, which gives it excellent ice-removal properties.

[0040] The fineness of the water-repellent fiber is preferably in the range of 1.5 dtex to 15 dtex, particularly 3.0 dtex to 8.0 dtex, similar to the core-sheath type composite fiber, and the fiber length of the water-repellent fiber is preferably in the range of 10 mm to 100 mm, particularly 20 mm to 80 mm.

[0041] The melting point of the sheath portion of the core-sheath composite fiber is preferably 30°C higher than the melting point of the sheath portion, specifically in the range of 220°C to 270°C, so that the sheath portion of the core-sheath composite fiber does not melt when it melts, just like the core portion of the core-sheath composite fiber.

[0042] (mixed fibers) In addition to the above combination of the sheath-core composite fiber and the water-repellent fiber, these may be further mixed with a mixed fiber similar to the sheath-core composite fiber, as long as the functions of the sheath-core composite fiber and the water-repellent fiber are not impaired. When a part of the water-repellent fiber is replaced with a popular mixed fiber, the cost can be kept low. Even in this case, the mixed fiber is PET fiber, since it has good bonding properties and is preferable from the viewpoint of recycling if it is made of the same material as the sheath-core composite fiber and the water-repellent fiber. This mixed fiber can be mixed in place of the water-repellent fiber. The fineness of this mixed fiber is preferably in the range of 1.5 dtex to 15 dtex, particularly 3.0 dtex to 8.0 dtex, similar to the water-repellent fiber. The fiber length of the mixed fiber is preferably in the range of 10 mm to 100 mm, particularly 20 mm to 80 mm. The melting point of the sheath portion of the core-sheath composite fiber is preferably 30°C higher than the melting point of the sheath portion, specifically in the range of 220°C to 270°C, so that the sheath portion of the core-sheath composite fiber does not melt when it melts, just like the core portion of the core-sheath composite fiber.

[0043] Furthermore, by using PET fiber for the core-sheath composite fiber, water-repellent fiber, and mixed fiber, it is possible to easily mix used fender liners as part of the material and use them with the new fender liner material of this embodiment.

[0044] (Proportion of each fiber) The total content of sheath-core composite fibers is preferably 50% by weight to 95% by weight, more preferably 60% by weight to 90% by weight, and even more preferably 70% by weight to 85% by weight. If the content of sheath-core composite fibers is less than 70% by weight, the shape stability of the fender liner molded into a three-dimensional shape cannot be sufficiently maintained. Conversely, if it exceeds 95% by weight, the content of water-repellent fibers, which play an important role in the ice releasability of the resulting film, is relatively low, making it difficult to sufficiently improve the ice releasability of the fender liner.

[0045] The content of the water-repellent fiber is preferably 5% by weight to 50% by weight, more preferably 10% by weight to 40% by weight, and further preferably 15% by weight to 30% by weight.

[0046] Also, a part of the water-repellent fiber can be replaced with mixed fiber. At least 5% by weight of water-repellent fiber is necessary, and the maximum amount to be replaced is up to 25% by weight, and it is particularly preferable to use 5% to 15% by weight. Since mixed fiber can be obtained at a lower cost than water-repellent fiber, it is cost-effective to increase the amount of mixed fiber. However, since the amount of water-repellent fiber is relatively small, the ice peeling property will be inferior. Therefore, the amount of mixed fiber can be set according to the required chipping resistance and ice peeling property.

[0047] (Entire fender liner) If the basis weight of the entire fender liner 10 including the main layer 13 and the produced film 15 (hereinafter simply referred to as the entire body) is too low, the effects of sound absorption and sound insulation cannot be expected, and conversely, if it is too high, the bonding strength of the core part of the core-sheath type composite fiber decreases. Therefore, the basis weight is set to 400 g / m including the produced film. 2 ~1600g / m 2 , especially 500g / m 2 ~1500g / m 2 , and even 700g / m 2 ~1300g / m 2 It is preferable to set the above.

[0048] The overall thickness (after molding) is preferably 1 mm to 15 mm, particularly 2 mm to 10 mm, and even more preferably 3 mm to 8 mm. If the overall thickness is less than 1 mm, the rigidity and shape retention of the fender liner 10 cannot be sufficiently ensured. Also, a large number of cells cannot be formed, and a sufficient sound absorbing effect cannot be achieved. Conversely, if the thickness exceeds 15 mm, the moldability of the fender liner 10 deteriorates, making it impossible to reduce the weight and resulting in increased costs.

[0049] If the overall airflow resistance is too high, sound absorption will be poor, and if it is too low, sound insulation will be poor. Therefore, it should be set at 100Ns / m 3 ~13,000Ns / m 3 , especially 500Ns / m 3 ~10,000Ns / m 3 In particular, when emphasis is placed on sound absorption in the low frequency range, the airflow resistance should be increased, and when emphasis is placed on sound absorption in the high frequency range, the airflow resistance should be decreased. The range of airflow resistance may be set to an appropriate value depending on the required sound absorption and sound insulation performance. The basis weight is 400 to 1600 g / m 2 As explained above, the range is preferable, but it is preferable to set the range so that the value of the allowable range of the airflow resistance moves to a larger value as the basis weight increases. That is, it is preferable to make the airflow resistance small when the basis weight is small, and to make the airflow resistance large when the basis weight is large. In particular, in this embodiment, since the generated film and the main layer are made of the same material as the substrate, it is considered that the above tendency (correlation between airflow resistance and basis weight) becomes prominent.

[0050] In this embodiment, excellent chipping resistance and excellent ice peeling properties are obtained, and specifically, it is preferable that the chipping resistance load is 150 kg or more, and particularly 200 kg or more. The upper limit of the chipping resistance load is within a range that can be predicted by a person skilled in the art, and it was determined that there is no need to set it. In addition, by including water-repellent fibers in the main body layer, water absorption from the tire house side can be suppressed, and by including water-repellent fibers in the generated film, ice peeling properties from the tire side are excellent. The ice peeling performance is preferably 30 N or less, particularly 25 N or less, and further preferably 20 N or less. In this embodiment, the unit "N" is "Newton".

[0051] At the same time, the resulting film and main layer improve the tensile strength, tear strength, bending strength, and other properties of the fender liner, resulting in excellent shape retention after molding. Therefore, when improved properties are not required, it is also possible to reduce the weight of the main layer. The tensile strength is preferably 90N or more, and particularly 120N or more. The tear strength is preferably 80N or more, and particularly 120N or more. The bending strength is preferably 1.5N or more on both the tire side and the tire house side. Although no upper limit is specified for either of these values, it is within a range that a person skilled in the art would be able to predict, and it was determined that there is no need to set an upper limit.

[0052] (Produced film) The resulting membrane, which is a feature of this embodiment, is formed by using a core-sheath type composite fiber as a substrate and applying heat and pressure to one side of the substrate to melt the sheath fiber. In other words, the resulting membrane is not formed by bonding a separate film material to the substrate. This eliminates the need to worry about adhesion with the substrate, and the resulting membrane can be manufactured integrally with the nonwoven fabric of the substrate, resulting in excellent productivity.

[0053] When the resulting film is formed, the sheath melts, making the core easier to move, and the cores come into closer contact with each other, i.e., face-to-face contact, resulting in a high density bond, resulting in a film with high surface rigidity while maintaining breathability. In addition, the surface of the resulting film is smooth and slippery, making it difficult for pebbles to adhere to or penetrate the surface. As a result, the fender liner is able to exhibit both high chipping resistance and excellent ice removal properties.

[0054] In this embodiment, the produced film contains water-repellent fibers and is configured to repel rainwater and muddy water scattered by tires on the road surface even when it splashes on the fender liner, preventing ice buildup and effectively preventing the outer surface of the fender liner from becoming soiled with mud, debris, etc. In particular, the surface of the produced film has a low average dynamic friction coefficient and is slippery, making it difficult for rainwater and muddy water to adhere to and penetrate, resulting in excellent ice-removal properties.

[0055] In addition, the resulting film has a high density and high rigidity, so the fender liner can be easily formed into a three-dimensional shape and has excellent resistance to deformation after forming.

[0056] In the resulting film, the molten sheath portion closes some of the voids in the core-sheath composite fiber, reducing air permeability and increasing density, making it possible to create a fender liner with superior sound absorption, sound insulation and rigidity.

[0057] In addition, because the produced film is breathable, it exhibits excellent sound absorption properties. That is, the produced film and main body layer of the fender liner absorb noise such as running noise generated between the tire and the road surface, impact noise generated when pebbles, sand, water, etc. kicked up by the tire hit the fender liner, and road noise, and can significantly reduce the transmission of such noise into the interior of the vehicle.

[0058] If the thickness of the produced film is too thick, it will have poor elongation and poor formability, and if it is too thin, it will not exhibit chipping resistance, so it is preferable that the thickness after molding is 0.05 mm to 2.0 mm, particularly 0.07 mm to 1.5 mm, and even more preferably 0.1 mm to 1.0 mm. If it is less than 0.05 mm, the produced film 15 will be very prone to tearing. On the other hand, if it exceeds 2.0 mm, the fluidity will be insufficient when heated and press-molded, and the produced film will not be able to follow the molding direction of the main layer, which may result in poor formability and a loss of sound absorbing effect against road noise.

[0059] The weight of the resulting film is preferably 50 g / m 2 ~300g / m 2 , especially 100 g / m 2 ~250g / m 2 50g / m 2 If the thickness is less than 300g / m, the layer of the generated film will be insufficient, resulting in thin areas and in some cases, areas where the layer itself does not exist. 2 If it exceeds this value, there is a high possibility that the sound absorbing effect will be impaired.

[0060] A method for manufacturing the fender liner of this embodiment will be described. A. Core-sheath type composite fibers, water-repellent fibers (or fibers mixed with other fibers) are discharged using the air-laying method to form a sheet-like substrate made of fibers, or the fibers that have been layered and stirred are entangled using a fleece machine or carding machine with a fiber spreader to form a sheet-like substrate made of fibers. B. Then, one side of the substrate is heated and pressurized, and held for a certain period of time to form a resulting film. Specifically, the resulting film is formed by any one of the following manufacturing methods. (1) After forming a plate-shaped substrate without a generated film, only one surface of the substrate is heated and molded into a plate-shaped substrate having a generated film using a press die; (2) forming a plate-shaped substrate without a generated film, and then passing one side of the substrate between rollers heated to form a plate; (3) After forming a plate-shaped substrate without a film, only one surface is heated and then the substrate is passed between rollers to form the substrate into a plate. C. The substrate having the produced film is then heated to make it easier to mold, and compressed and molded in a cold press mold for the fender liner while being cooled.

[0061] (Fender liner manufacturing conditions) (Substrate manufacturing conditions) The conditions for laminating and mixing the core-sheath composite fiber and the water-repellent fiber (or a mixture of additional fibers) together at the same time are similar to the manufacturing method and manufacturing conditions for a general substrate, and a detailed explanation will be omitted here. (Conditions for forming the generated film) If the heating temperature for forming the generated film is too low, the required generated film cannot be formed, and conversely, if it is too high, the film thickness becomes thick, elongation becomes poor, and moldability becomes poor. Therefore, the heating temperature of the heating press is preferably 180°C to 240°C, particularly 190°C to 230°C. In addition, when passing through rollers with one side heated instead of a press machine, the time is short, so the temperature can be made higher. If the heating time is short, the required generated film cannot be obtained, and if it is long, the film thickness becomes thick, elongation becomes poor, and moldability becomes poor. Therefore, the heating time is preferably 0.5 seconds to 30 seconds, particularly 1.0 seconds to 25 seconds. The interval between the press mold or rollers is preferably 0.3 mm to 15 mm, particularly 0.5 mm to 10 mm. When passing through rollers with one side heated, the time is short, so the interval between the rollers is preferably narrow. In particular, the thickness and strength of the generated film can be adjusted by controlling the heating temperature, heating time, pressure applied, pressure gap, etc., so that the properties according to the use, etc. can be easily adjusted.

[0062] The predetermined thickness when one surface of the substrate is heated and compressed is preferably 5 to 100 times the thickness before compression. After the film is formed, it is considered that the thickness is restored to 1.0 to 0.6 times the thickness before compression, but the thickness varies depending on the location, making it difficult to specify the restored thickness accurately, and the restored thickness was specified empirically.

[0063] (Fender liner molding conditions) In order to mold a plate-shaped substrate into a predetermined shape, the substrate is heated in a heating furnace or the like to make it easier to mold (deform), and the heated substrate is placed in a cold press mold of a predetermined shape to be molded. In this case, it is preferable to cool the substrate as quickly as possible after molding into a predetermined shape in the press mold so that the shape can be maintained, so that cooling air may be blown from the surface of the press mold to cool the heated substrate while molding. The heating temperature may be any temperature that makes the plate-shaped substrate easy to mold, and may be any temperature higher than the melting point of the sheath of the composite fiber, and does not need to be very high. For example, it is preferable to set the temperature in the range of 120°C to 240°C, particularly 130°C to 220°C, and further 150°C to 200°C. The heating time may be any time required to make the substrate easy to mold, so it is preferable to set the heating time in the range of 10 seconds to 60 seconds, particularly 20 seconds to 50 seconds.

[0064] The die clearance of the cold press die may be appropriately selected and set depending on the thickness of the substrate, the fibers of the nonwoven fabric, or the application, but a practical range is 1.0 mm to 10 mm, particularly about 2.0 mm to 5.0 mm. Although the above describes an example of molding using a cold press die, the manufacturing method is not limited to this, and for example, molding may be performed using a hot press die.

[0065] Since the produced film and the substrate are made of the same material, they will not peel off during molding, and it is possible to obtain a product that has good moldability, increased strength, and excellent shape retention.

[0066] In addition, since the film is once formed and solidified, even if the entire product is heated to facilitate molding, the film remains, so that a stable film is formed. EXAMPLES

[0067] EXAMPLES The present invention will be specifically described below with reference to examples. The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0068] Example 1 The main fiber is a core-sheath type composite fiber, and both the core and sheath parts are made of PET fibers with a fineness of 4.4 dtex and a fiber length of 51 mm. The melting point of the core part is 240°C, and the melting point of the sheath part is 110°C. The water-repellent fiber is a PET fiber with a melting point of 240°C, a fineness of 6.6 dtex, and a fiber length of 51 mm. A fluorine-based water-repellent agent is applied to the surface of this PET fiber.

[0069] The composite fiber is 80% by weight of sheath type composite fiber and 20% by weight of water repellent fiber, and the total weight is 700g / m 2 A fiber web with a thickness of 20 mm was produced by the air-laying method so that one surface of the fiber web was heated (heating temperature: about 220°C, heating time: 5 seconds) and pressed while maintaining the mold gap at 5.0 mm to form a produced membrane. Thickness of restored substrate after formation of generated film: 16mm Film thickness: 0.2mm~0.3mm Weight of the resulting film: 200g / m 2

[0070] Before and after heating and compressing in a press die, the thickness of the substrate was restored to 1.0 to 0.6 times its original thickness. The restored thickness differed in different areas, so the above ranges are shown. Roughly speaking, the restored thickness was 0.8 times its original thickness. From this restored state, it can be said that only the surface of the substrate was melted and solidified, resulting in a high-density, thin film.

[0071] The substrate with the resulting film is heated to make it easier to mold, and then molded into the shape of a fender liner in a mold for the fender liner. Specifically, before placing the substrate with the resulting film into the mold, the entire substrate with the resulting film is heated in a heating furnace (heating temperature: approximately 180°C, heating time: 40 seconds) to soften it so that it is easier to mold. It is then pressed in a cold press mold with a gap of 4.0 mm to mold it into the shape of a fender liner. The fender liner obtained after molding has a total overall thickness (total thickness) of 4.0 mm and an overall basis weight of 700 g / m 2 The airflow resistance is 340Ns / m 3It was.

[0072] Incidentally, since the thickness of the main layer and the generated film are not uniform, the thickness is taken as the average thickness over the whole, but it may be taken as the average thickness over the majority of the layers.

[0073] Example 2 Example 2 differs from Example 1 in that a portion of the water-repellent fiber was replaced with mixed fiber, but the rest is the same as Example 1. In Example 2, 10% by weight of the water-repellent fiber was replaced with mixed fiber having a fineness of 6.6 dtex and a fiber diameter of 64 mm, making the water-repellent fiber 10% by weight and the mixed fiber 10% by weight. The core-sheath type composite fiber remains at 80% by weight.

[0074] As a method for producing the produced membrane, a heated press mold was used in Example 1, but in Example 2, the fiber web was passed between one heated roller and the other roller at room temperature, and heated and pressurized. The heating temperature was 220°C, the heating time was 5 seconds, and the gap between the rollers was 3 mm.

[0075] The entire fiber web was then heated in a heating furnace (heating temperature: about 180°C, heating time: 40 seconds) to make it easier to mold, and then molded into the desired shape using a cold press mold with a gap of 4 mm. The resulting fender liner had a total thickness of 4.0 mm and an overall basis weight of 700 g / m 2 The airflow resistance is 214Ns / m 3 The thickness of the generated film was 0.2mm to 0.3mm, and the weight of the generated film was 200g / m 2 It was.

[0076] Example 3 The difference between Example 3 and Example 2 is that in Example 3, the total basis weight is 1000 g / m 2 The rest of the film, including the manufacturing method, was the same as in Example 2. The thickness of the film was 0.2 mm to 0.3 mm, and the basis weight of the film was 200 g / m 2 The airflow resistance was 398Ns / m 3 It was.

[0077] Example 4 The difference between Example 4 and Example 2 is that the core-sheath type composite fiber is 80% by weight, the water-repellent fiber is 20% by weight, and the total basis weight is 1100 g / m 2 The rest of the film, including the manufacturing method, was the same as in Example 2. The thickness of the film was 0.2 mm to 0.3 mm, and the basis weight of the film was 200 g / m 2 The airflow resistance was 572.5Ns / m 3 It was.

[0078] (Examples 5 to 7) In Examples 5 to 7, the core-sheath type composite fiber, water-repellent fiber, and mixed fiber were all in the same proportions as in Example 2, with the difference being that the overall thickness of Examples 5, 6, and 7 was 4 mm, 2 mm, and 2 mm, respectively, and the overall basis weight was 1200 g / m 2 , 700g / m 2 , 900g / m 2 The thickness of the generated film is 0.3mm to 0.5mm, and the weight of the generated film is 200g / m 2 The airflow resistance of each of Examples 5, 6 and 7 was 590 Ns / m 3 , 354Ns / m 3 , 688Ns / m 3 It was.

[0079] (Examples 8 and 9) Examples 8 and 9 differ from Example 2 in that in Example 8, one of the dies was pressed against a press mold heated to 220°C for 5 seconds, whereas in Example 9, one of the dies was pressed against a press mold heated to 220°C for 20 seconds to form a generated film, and the overall thickness of Examples 8 and 9 was both 5 mm. The rest was the same as Example 2.

[0080] Example 10 Example 10 differs from Example 2 in that the core-sheath type composite fiber is 90% by weight and the water-repellent fiber is 10% by weight.

[0081] Below, a description will be given of Examples 11 to 25. The types and blending ratios of each fiber, various performances, and the like of Examples 11 to 25 are as shown in Fig. 9, but a brief description will be given.

[0082] Example 11 Example 11 differs from Example 2 in that the core and sheath of the core-sheath composite fiber both use PET fibers with a fineness of 4.4 dtex and a fiber length of 64 mm. The melting point of the core is 240°C, and the melting point of the sheath is 110°C. Example 11 also differs from Example 2 in that the water-repellent fiber uses PET fibers with a melting point of 240°C, a fineness of 6.6 dtex, and a fiber length of 51 mm, and the mixed fiber uses PET fibers with a melting point of 260°C, a fineness of 6.6 dtex, and a fiber diameter of 51 mm. Example 11 also differs from Example 2 in that the core-sheath composite fiber is 70% by weight, the water-repellent fiber is 5% by weight, and the mixed fiber is 25% by weight.

[0083] The method for producing the produced membrane was to pass the fiber web between one heated roller and the other roller at room temperature and apply heat and pressure to it, similarly to Example 2. The heating temperature was 220° C., the heating time was 5 seconds, and the gap between the rollers was 0.5 mm.

[0084] The fiber web on which the produced film was formed as described above was heated in a heating furnace (heating temperature: about 200°C, heating time: 20 seconds) to make it easier to mold, and then molded into a predetermined shape using a cold press mold with a gap of 4 mm. The rest was the same as in Example 2.

[0085] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 700 g / m 2 The airflow resistance is 232Ns / m 3 The thickness of the generated film was 0.51 mm, and the weight of the generated film was 152 g / m 2 It was.

[0086] Example 12 Example 12 differs from Example 11 in that the core of the sheath-core composite fiber is a PET fiber with a melting point of 220° C., and the water-repellent fiber is a PET fiber with a melting point of 220° C., a fineness of 6.6 dtex, and a fiber length of 80 mm. Example 12 also differs from Example 11 in that the sheath-core composite fiber is 50% by weight, and the water-repellent fiber is 50% by weight.

[0087] The manufacturing method of the produced membrane differs from that of Example 11 in that the heating temperature of one of the heated rollers was 200°C and the heating time was 8 seconds. The fiber web on which the produced membrane was formed was heated in a heating furnace (heating temperature: about 160°C, heating time: 50 seconds) to make it easier to mold, and was molded into a predetermined shape using a cold press mold with a gap of 4 mm. The rest is the same as that of Example 11.

[0088] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 1000 g / m 2 The airflow resistance is 638Ns / m 3 The thickness of the generated film was 0.81 mm, and the weight of the generated film was 241 g / m 2 It was.

[0089] (Example 13) Example 13 differs from Example 11 in that the core of the sheath-core composite fiber had a melting point of 260° C., the sheath was made of PET fiber with a melting point of 120° C., the water-repellent fiber was made of PET fiber with a melting point of 260° C. and a fiber length of 80 mm, and the mixed fiber was made of PET fiber with a fiber length of 64 mm. Example 13 also differs from Example 11 in that the core-sheath composite fiber was 60% by weight, the water-repellent fiber was 30% by weight, and the mixed fiber was 10% by weight.

[0090] The manufacturing method of the produced membrane is as follows: the heating temperature of one of the heated rollers is 200°C, and the heating time is 6 seconds. The fiber web on which the produced membrane is formed is heated in a heating furnace (heating temperature: about 220°C, heating time: 15 seconds), and molded into a predetermined shape using a cold press mold with a gap of 4 mm. The rest is the same as in Example 11.

[0091] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 1000 g / m 2 The airflow resistance is 642Ns / m 3 The thickness of the generated film was 0.84 mm, and the weight of the generated film was 246 g / m 2 It was.

[0092] Example 14 Example 14 differs from Example 11 in that the core-sheath composite fiber used was a PET fiber with a fiber length of 51 mm, and the mixed fiber used was a PET fiber with a fiber length of 64 mm. Example 14 also differs from Example 11 in that the core-sheath composite fiber was 70% by weight, the water-repellent fiber was 10% by weight, and the mixed fiber was 20% by weight.

[0093] The method for producing the resulting membrane was the same as in Example 11, except that the heating temperature of the heating furnace for heating the entire fiber web was about 220° C. and the heating time was 20 seconds.

[0094] The resulting fender liner had a total thickness of 6.0 mm and a total weight of 1000 g / m 2 The airflow resistance is 435Ns / m 3 The thickness of the generated film was 1.01 mm, and the weight of the generated film was 300 g / m 2 It was.

[0095] Example 15 Example 15 differs from Example 11 in that the core of the sheath-core composite fiber is a PET fiber with a melting point of 260° C., and the water-repellent fiber is a PET fiber with a melting point of 260° C. and a fiber length of 64 mm. Example 15 also differs from Example 11 in that the sheath-core composite fiber is 70% by weight, the water-repellent fiber is 30% by weight, and there is no mixed fiber.

[0096] The manufacturing method of the produced membrane in Example 15 is different from that in Example 11 in that the distance between the cold press dies is 5 mm. The rest is the same as that in Example 11.

[0097] The resulting fender liner had a total thickness of 6.0 mm and a total weight of 1,300 g / m 2 The airflow resistance is 899Ns / m 3 The thickness of the generated film was 1.22 mm, and the weight of the generated film was 250 g / m 2 It was.

[0098] Example 16 Example 16 differs from Example 11 in that the core-sheath composite fiber is a PET fiber having a fineness of 6.6 dtex and a fiber length of 64 mm, the water-repellent fiber is a PET fiber having a fineness of 4.4 dtex and a fiber length of 80 mm, and the mixed fiber is a PET fiber having a fineness of 6.6 dtex and a fiber length of 80 mm. Example 16 also differs from Example 11 in that the core-sheath composite fiber is 80% by weight, the water-repellent fiber is 15% by weight, and the mixed fiber is 5% by weight. The rest is the same as Example 11. The production method of the produced membrane is the same as Example 11.

[0099] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 1000 g / m 2 The airflow resistance is 763Ns / m 3 The thickness of the generated film was 0.76 mm, and the weight of the generated film was 233 g / m 2 It was.

[0100] (Example 17) Example 17 differs from Example 11 in that it contains 90% by weight of core-sheath type composite fiber, 10% by weight of water-repellent fiber, and no mixed fiber. The rest is the same as Example 11. The manufacturing method of the produced membrane is also the same as Example 11.

[0101] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 1000 g / m 2 The airflow resistance is 821Ns / m 3 The thickness of the generated film was 0.91 mm, and the weight of the generated film was 278 g / m 2 It was.

[0102] (Example 18) Example 18 differs from Example 11 in that it contains 95% by weight of core-sheath type composite fiber, 5% by weight of water-repellent fiber, and no mixed fiber. The rest is the same as Example 11. The manufacturing method of the produced membrane is also the same as Example 11.

[0103] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 700 g / m 2The airflow resistance is 290Ns / m 3 The thickness of the generated film was 0.63 mm, and the weight of the generated film was 184 g / m 2 It was.

[0104] (Example 19) Example 19 differs from Example 11 in that the fineness of the core-sheath composite fiber is 3.0 dtex, the fineness of the water-repellent fiber is 3.0 dtex, the fineness of the mixed fiber is 4.4 dtex, and the core-sheath composite fiber is 80% by weight, the water-repellent fiber is 10% by weight, and the mixed fiber is 10% by weight. The rest is the same as Example 11. The manufacturing method of the produced membrane is the same as Example 11, except that the distance between the press molds is 4.0 mm.

[0105] The resulting fender liner had a total thickness of 10.0 mm and a total weight of 1500 g / m 2 The airflow resistance is 1015Ns / m 3 The thickness of the generated film was 1.50 mm, and the weight of the generated film was 250 g / m 2 It was.

[0106] (Example 20) Example 20 differs from Example 11 in that the fineness of the sheath-core composite fiber is 8.0 dtex, the fiber length is 30 mm, the fineness of the water-repellent fiber is 6.6 dtex, the fiber length is 64 mm, the fineness of the mixed fiber is 4.4 dtex, the fiber length is 51 mm, the core-sheath composite fiber is 80 weight %, the water-repellent fiber is 15 weight %, and the mixed fiber is 5 weight %. The rest is the same as Example 11. The manufacturing method of the produced membrane is also the same as Example 11.

[0107] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 700 g / m 2 The airflow resistance is 145Ns / m 3 The thickness of the generated film was 0.55 mm, and the weight of the generated film was 161 g / m 2 It was.

[0108] Example 21 Example 21 differs from Example 11 in that the fineness of the sheath-core composite fiber is 8.0 dtex, the fiber length is 80 mm, the fineness of the water-repellent fiber is 6.6 dtex, the fiber length is 30 mm, the fineness of the mixed fiber is 6.6 dtex, the fiber length is 30 mm, and the core-sheath composite fiber is 80 weight %, the water-repellent fiber is 10 weight %, and the mixed fiber is 10 weight %. The rest is the same as Example 11. The manufacturing method of the produced membrane is the same as Example 11, except that the distance between the press molds is 1.5 mm.

[0109] The resulting fender liner had a total thickness of 8.0 mm and a total weight of 1,300 g / m 2 The airflow resistance is 319Ns / m 3 The thickness of the generated film was 0.92 mm, and the weight of the generated film was 284 g / m 2 It was.

[0110] Example 22 Example 22 differs from Example 11 in that the fineness of the sheath-core composite fiber is 12.0 dtex, the fiber length is 30 mm, the fineness of the water-repellent fiber is 8.0 dtex, the fiber length is 20 mm, the fineness of the mixed fiber is 8.0 dtex, the fiber length is 20 mm, the core-sheath composite fiber is 80 weight %, the water-repellent fiber is 10 weight %, and the mixed fiber is 10 weight %. The rest is the same as Example 11. The manufacturing method of the produced membrane is the same as Example 11 except that the distance between the press molds is 1.0 mm.

[0111] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 1200 g / m 2 The airflow resistance is 421Ns / m 3 The thickness of the generated film was 0.62 mm, and the weight of the generated film was 193 g / m 2 It was.

[0112] Example 23 Example 23 differs from Example 11 in that the fineness of the sheath-core composite fiber is 12.0 dtex, the fiber length is 51 mm, the fineness of the water-repellent fiber is 8.0 dtex, the fiber length is 12 mm, the fineness of the mixed fiber is 8.0 dtex, the fiber length is 51 mm, the core-sheath composite fiber is 80 weight %, the water-repellent fiber is 10 weight %, and the mixed fiber is 10 weight %. The rest is the same as Example 11. The manufacturing method of the produced membrane is also the same as Example 11.

[0113] The resulting fender liner had a total thickness of 4.0 mm and a total weight of 700 g / m 2 The airflow resistance is 116Ns / m 3 The thickness of the generated film was 0.61 mm, and the weight of the generated film was 179 g / m 2 It was.

[0114] Example 24 Example 24 differs from Example 11 in that it contains 80% by weight of core-sheath type composite fiber, 10% by weight of water-repellent fiber, and 10% by weight of mixed fiber. The rest is the same as Example 11. The manufacturing method of the produced membrane is the same as Example 11 except that the gap between the press dies is 1.0 mm.

[0115] The resulting fender liner had a total thickness of 6.0 mm and a total weight of 1000 g / m 2 The airflow resistance is 290Ns / m 3 The thickness of the generated film was 0.12 mm, and the weight of the generated film was 50 g / m 2 It was.

[0116] (Example 25) Example 25 differs from Example 11 in that the fineness of the water-repellent fiber is 4.4 dtex, the fineness of the mixed fiber is 4.4 dtex, the core-sheath type composite fiber is 80% by weight, the water-repellent fiber is 10% by weight, and the mixed fiber is 10% by weight. The rest is the same as Example 11. The manufacturing method of the produced membrane is the same as Example 11, except that the roller gap is 1.0 mm and the press mold gap is 5.0 mm.

[0117] The resulting fender liner had a total thickness of 8.0 mm and a total weight of 1200 g / m 2 The airflow resistance is 435Ns / m 3 The thickness of the generated film was 0.25 mm, and the weight of the generated film was 82 g / m 2 It was.

[0118] Next, comparative examples 1 to 3 will be described with reference to FIG.

[0119] Comparative Example 1 Comparative Example 1 is a nonwoven fabric made of coarse felt (for example, made by finely shredding waste clothing into a felt-like material, and made from raw materials such as cotton, synthetic fibers, and wool) with a PP resin film bonded to it. In Comparative Example 1, since the PP resin film is provided, no generated membrane is formed.

[0120] The nonwoven fabric has a fineness of 2dtex to 7dtex, a thickness of 3.5mm, and a basis weight of 800g / m 2 The PP resin film is 0.5 mm thick and has a basis weight of 170 g / m 2 The overall thickness is 4.0mm and the weight is 970g / m 2 , ventilation resistance is 625Ns / m 3 It was of.

[0121] Comparative Example 2 Comparative Example 2 does not contain water-repellent fibers, but is made of 90% core-sheath fibers by weight and 10% mixed fibers by weight, with an overall thickness of 4.0 mm. The rest is the same as Example 2. The ice peeling load of Comparative Example 2 was compared with that of the examples of the present invention. Details will be explained in the section on ice peeling load, but the ice peeling load of Comparative Example 2 was a large load of 37.1 N. It was confirmed that with Comparative Example 2, which does not contain water-repellent fibers, the ice that had adhered to it was difficult to peel off.

[0122] Comparative Example 3 Comparative Example 3 is a cold molded product with 80% by weight of core-sheath fiber, 10% by weight of water-repellent fiber, and 10% by weight of mixed fiber without forming a formed film. In Comparative Example 3 without a formed film, the ice peeling load was a high value of 64.1 N, and it was recognized that it was difficult to peel. In addition, the average dynamic friction coefficient was 0.37, which resulted in a non-slip surface, and it was recognized that the chipping resistance was also poor.

[0123] (Various tests and their measurement results) FIG. 4 shows in a table the fiber ratio, fiber diameter, fiber length, thickness of the produced membrane, overall thickness, etc., of each example and each comparative example.

[0124] FIG. 5 shows, in a table, the results of measuring various performances and the manufacturing methods etc. for Examples 1 to 4 and Comparative Example 1.

[0125] 5, it was confirmed that Examples 1 to 4 showed excellent results in all of the tensile strength, tear strength, flexural strength, chipping resistance, and icing peeling load, similar to Comparative Example 1. That is, Comparative Example 1 satisfied various performance requirements by adhering a PP film to a substrate, but this Example confirmed that it was possible to obtain a product that satisfied various performance requirements by melting and solidifying the surface of the substrate, without adopting the method of Comparative Example 1, that is, the method of laminating a film of a different material to the substrate.

[0126] FIG. 6 shows a 50x microscopic cross-sectional photograph of the sample of Example 3. In FIG. 6, the upper side is the generated film side, and the lower side is the back side. The part close to the upper surface is the generated film, and the part below this is the main layer. However, the boundary between the main layer and the generated film is not clear even when looking at the microscopic photograph, so the original thickness part when the generated film was formed is judged to be the generated film, and the part below that, from the generated film-approximate part of the white part to the back side layer, is considered to be the main layer. The main layer is divided, for example, into the lower most back side layer and the generated film-approximate part close to the generated film on the upper surface, and the intermediate layer between the most back side layer and the generated film-approximate part. The reason for this division is thought to be the difference in the cooling state during molding. Specifically, when the entire heated substrate is set in a cold mold, the back side directly contacts the mold surface and is immediately cooled, but the upper surface side is cooled by the mold through the generated film, resulting in a difference in the cooling and solidification state. As a result, in the back side layer, the fibers are solidified in a coarse state, but the part close to the generated film is dense with the sheath part spreading around the core part, and becomes a generated film approximation part close to the generated film. The middle part is a mixture of white and black parts, and the density is also intermediate. Note that this micrograph is just one example, and not all are necessarily divided in this way. For example, when the overall thickness is thin, the heating temperature or heating time is short, and it may not be possible to separate into each layer. For example, there may be cases where the most back side layer and the intermediate layer have almost the same cross section, or the generated film approximation layer is hardly visible.

[0127] (Icing test) The ice adhesion test method was the same as that disclosed in JP 2011-240821 A, so a detailed description will be omitted. The shear force required to shear the ice attached to the sample with the pushing member was measured. In this example, this shear force is called the ice adhesion detachment load.

[0128] The ice peeling load was tested using samples from multiple examples and multiple comparative examples. Specifically, the tests were conducted on Examples 1 to 4, 8 to 10, and Comparative Examples 1 to 3. As a result, the ice peeling loads for Examples 1 to 4 and 8 to 10 were 10.4N, 9.5N, 8.9N, 8.9N, 9.2N, 9.0N, and 9.2N, respectively, all of which were less than 20N, showing excellent ice peeling loads and indicating that ice was not only difficult to form but also easy to peel off. In addition, since Comparative Example 1 had a PP film attached, the ice peeling load was an excellent value of 4.2N. In contrast, Comparative Examples 2 and 3 had fairly high ice peeling loads of 37.1N and 64.1N. Comparative Example 3 did not have a generated film, and did not have a film like Comparative Example 1, so it is believed that the ice peeling load was quite high. In addition, Comparative Example 2 had a generated film, but the high value of 30N or more was believed to be due to the fact that the generated film did not contain water-repellent fibers.

[0129] (Chipping resistance) The chipping resistance is a value obtained based on a chipping resistance test. The chipping resistance test was a performance test using a nut drop method in which a number of brass nuts weighing 0.45 g equivalent to 3 kg were dropped from a height of 2 m onto a test piece of a given size. The nuts (each drop was 3 kg) were dropped 50 times, and the presence or absence of exposure of the base layer, depression of the entire material, or deformation was observed. The total load resulting from dropping the nuts (each drop was 3 kg) 50 times was 150 kg, and this load was taken as the chipping resistance load in this embodiment and comparative example. The number of drops was further increased until damage was observed in the generated film, and the number of drops was measured.

[0130] The above measurements were carried out for the samples of Examples 1 to 4 and Comparative Example 1. The results are shown in FIG. 5. In all of Examples 1 to 4 and Comparative Example 1, no damage such as exposure of the main body layer, depression of the entire material, or deformation was observed after 50 times. Furthermore, the number of times until damage was observed in the generated film was 70 times, 70 times, 120 times, and 130 times in Examples 1 to 4, respectively. In Comparative Example 1, it was 130 times. The required performance is sufficient if it is 50 times or more, and all of them satisfied the required performance. It was confirmed that both Examples 1 to 4 and Comparative Example 1 had excellent chipping resistance.

[0131] However, Comparative Example 1 had a two-layer structure of nonwoven fabric and PP film, and therefore could not satisfy the requirements in other performance aspects.

[0132] Although no measurement was performed for Comparative Example 3, since no film was formed, it was clearly predicted that good results would not be obtained in terms of chipping resistance, and therefore the test was omitted.

[0133] (Average dynamic friction coefficient) The average dynamic friction coefficient was measured using a multi-function friction measuring instrument TL201Tt manufactured by Trinity Lab Co., Ltd. The measurement data was used to calculate the average dynamic friction coefficient using triboanalysis software. The samples of Examples 8 and 9 and Comparative Example 3 were tested. The results are shown in Figures 7A and 7B. Figure 7A shows the measurement results of Comparative Example 3 and Example 8, and Figure 7B shows the measurement results of Comparative Example 3 and Example 9. If Examples 8 and 9 were shown on the same graph, they would overlap and be difficult to see, so they were separated. As shown in Figure 7A, the variation in the dynamic friction coefficient is significantly different between Example 8 and Comparative Example 3, and when the average dynamic friction coefficient was calculated, it was 0.22 for Example 8 and 0.37 for Comparative Example 3, showing a large difference. The same is true for Figure 7B, where Example 9 was 0.22 and Comparative Example 3 was 0.37, showing a large difference.

[0134] The reason why the average dynamic friction coefficient was good in Examples 8 and 9, but poor in Comparative Example 3, can be attributed to the absence of a generated film and the lack of water-repellent fibers in Comparative Example 3. That is, it is believed that by providing a generated film and including water-repellent fibers in Examples 8 and 9, an excellent average dynamic friction coefficient was obtained, the surface became smooth, and the chipping resistance improved when pebbles were repelled, and excellent ice removal properties were obtained.

[0135] The average dynamic friction coefficients of Examples 1 to 7 and Example 10 were measured in the same manner as Example 8. The results were 0.23, 0.24, 0.23, 0.22, 0.24, 0.24, 0.22, and 0.24, respectively, in Examples 1 to 7 and 10, all of which were less than 0.3. It is believed that by providing a generated film and including water-repellent fibers in the generated film, Examples 1 to 7 and 10 were able to obtain an excellent average dynamic friction coefficient, resulting in a smooth surface and excellent ice removal properties.

[0136] In Examples 8 and 9, the temperature was 220°C in the press mold when the resulting film was formed, but the holding time was 5 seconds in Example 8 and 20 seconds in Example 9. 2 , 200g / m 2 The thickness of the generated film was 0.2mm to 0.3mm, and it is believed that there was little difference in the generated film and therefore no difference in the average dynamic friction coefficient. In addition, the ice peeling load was 9.2N for Example 8 and 9.0N for Example 9, and there was almost no difference.

[0137] (Tensile strength) Tensile strength was measured for some of the Examples and some of the Comparative Examples. The size of the sample to be measured was 250 mm×150 mm, the span was 100 mm, and the test speed was 50 mm / min, and the tensile strength was measured in accordance with JIS K 7161.

[0138] In Examples 1 to 4, the values ​​were 140N, 126N, 232N, and 236N, and in Comparative Example 1, the value was 315N. All of the values ​​were 90N or more, and in particular, 120N or more, and it was confirmed that all of the values ​​showed excellent performance.

[0139] (tear strength) The sample size was 50 mm x 150 mm, the span was 100 mm, the test speed was 50 mm / min, and the tear strength was measured in accordance with JIS K 7128.

[0140] In Examples 1 to 4, the strengths were 140N, 126N, 232N, and 236N, and in Comparative Example 1, the strength was 315N, all of which were 80N or more, especially 120N or more, and it was confirmed that all of them showed excellent performance. However, Comparative Example 1 had a two-layer structure of nonwoven fabric and PP film, and therefore could not satisfy the requirements in other performances.

[0141] (Bending strength) The sample size was 50 mm × 150 mm, the span was 100 mm, the test speed was 50 mm / min, and the bending strength was measured in accordance with JIS K 7171.

[0142] In Examples 1 to 4, the bending strength on the tire side was 4.5 N, 6.2 N, 11.3 N, and 15.2 N, and in Comparative Example 1, it was 22.3 N. All of them were 1.5 N or more, especially 2.0 N or more, and it was confirmed that all of them showed excellent performance.

[0143] In addition, in Examples 1 to 4, the bending strength on the body side (tire house side) was 2.4 N, 3.5 N, 5.9 N, and 8.5 N, while in Comparative Example 1 it was 11.3 N, all of which were 1.5 N or more, particularly 2.0 N or more, and it was confirmed that all of them showed excellent performance. However, Comparative Example 1 had a two-layer structure of nonwoven fabric and PP film, and therefore did not satisfy the requirements in other performances.

[0144] (Vertical incidence sound absorption coefficient) For Examples 1, 3, and 6, the normal incidence sound absorption coefficient was measured in the frequency range of 500 Hz to 6300 Hz in accordance with JIS A 1405-2 using a measuring device manufactured by Bruel & Kjær AG. It was confirmed that the sound absorption coefficients of Examples 1, 3, and 6 were the predicted sound absorption coefficients, as shown in Figure 8, and that satisfactory results were obtained. It was confirmed that the predicted data could be obtained for sound absorption performance in this example.

[0145] (Method of measuring airflow resistance) The airflow resistance was measured using a measuring device "KSE-F8-AP1" manufactured by Kato Tech Co., Ltd., based on the measuring method (JIS L 1096) disclosed in the instruction manual for this device. The measurement sample size was 40 mm in diameter. The specific measuring method is disclosed in Japanese Patent No. 6082145, so it will not be described here.

[0146] The airflow resistance of Examples 1 to 7 was 340 Ns / m 3 , 214Ns / m 3 , 398Ns / m 3 , 572.5Ns / m 3 , 590Ns / m 3 , 354Ns / m 3 , 688Ns / m 3 The comparative example 1 is 625Ns / m 3 The airflow resistance was as predicted in Examples 1 to 7 and Comparative Example 1, and did not pose any practical problems.

[0147] Various performances of Examples 11 to 25 will be briefly described with reference to FIG.

[0148] For Examples 11 to 25, the chipping resistance, average dynamic friction coefficient, bending strength, tensile strength, tear strength, icing peeling load, and the presence or absence of damage were measured in the same manner as in Example 1.

[0149] In Examples 11 to 25, the average dynamic friction coefficient was 0.30 or less in all cases, and it is believed that the excellent average dynamic friction coefficient was obtained in Examples 11 to 25 by providing a generated film and including water-repellent fibers in the generated film. Because the average dynamic friction coefficient was excellent, the surface was smooth, and the ice peeling load was 30 N or less in all cases, which is believed to be why excellent ice peeling properties were obtained.

[0150] In Examples 11 to 25, the tensile strength, tear strength, and bending strength were all satisfactory, and the requirements for a fender liner were met. Furthermore, in a damage test similar to that of Example 1, no damage was observed in Examples 11 to 25. [Industrial Applicability]

[0151] The present invention is advantageously applicable to a vehicle fender liner and a manufacturing method thereof. [Explanation of symbols]

[0152] 1 vehicle 2 Tires 3 Wheelhouse 10 Fender liner 11 Fiber web (base material) 13 Body layer 15 Generated film 17 Core-sheath composite fiber 18 Water-repellent fibers t Gap

Claims

1. The substrate is a core-sheath type composite fiber in which both the core and sheath are made of PET fibers, and the sheath is melted and solidified to bond the core to form a fiber web, The core-sheath type composite fiber accounts for 50% by weight to 95% by weight of the total weight of the fiber, and the water-repellent fiber made of PET fiber accounts for 5% by weight to 50% by weight of the total weight of the fiber, the water-repellent fibers are dispersed and mixed in the sheath portion of the core-sheath type composite fiber, A film having a high density and air permeability is provided on one surface of the fiber web by melting and solidifying the sheath portion, The layers other than the generated film are a main layer having a lower density than the generated film, The thickness of the generated film is thinner than the thickness of the main layer, The water-repellent fibers are dispersed and mixed in the molten and solidified sheath portions of both the generated film and the main body layer, A fender liner for a vehicle, characterized in that the main body layer is formed into a fender liner shape so that the main body layer faces the tire house side and the generated film forms the outermost surface on the tire side.

2. 2. The vehicle fender liner according to claim 1, A fender liner for a vehicle, characterized in that a part of the water-repellent fiber is replaced with a mixed fiber made of PET fiber so that at least 5% by weight of the water-repellent fiber remains.

3. 2. The vehicle fender liner according to claim 1, The produced film has an average dynamic friction coefficient of 0.3 or less, a thickness of 0.05 mm to 2.0 mm, and a basis weight of 50 g / m 2 Up to 300 g / m 2 and Overall thickness including the produced film: 1.0 mm to 15 mm, basis weight: 400 g / m 2 ~1600g / m 2 A fender liner for a vehicle, characterized in that the fender liner has a chipping load resistance of 150 kg or more and an ice peeling load of 30 N or less.

4. 3. The vehicle fender liner according to claim 2, The produced film has an average dynamic friction coefficient of 0.3 or less, a thickness of 0.05 mm to 2.0 mm, and a basis weight of 50 g / m 2 Up to 300 g / m 2 and Overall thickness including the produced film: 1.0 mm to 15 mm, basis weight: 400 g / m 2 ~1600g / m 2 A fender liner for a vehicle, characterized in that the fender liner has a chipping load resistance of 150 kg or more and an ice peeling load of 30 N or less.

5. The vehicle fender liner according to any one of claims 1 to 4, A vehicle fender liner, characterized in that the core of the sheath-core composite fiber is a PET fiber having a fineness of 1.5 dtex to 15 dtex, a fiber length of 10 mm to 100 mm, and a melting point of 220°C to 270°C, which is 30°C or more higher than the melting point of the sheath, and the sheath has a fineness of 1.5 dtex to 15 dtex, a fiber length of 10 mm to 100 mm, and a melting point of 90°C to 180°C.

6. 6. The vehicle fender liner according to claim 5, The water-repellent fiber is a PET fiber having a fineness of 1.5 dtex to 15 dtex, a fiber length of 10 mm to 100 mm, and a melting point of 220°C to 270°C.

7. 7. The vehicle fender liner according to claim 6, A fender liner for a vehicle, characterized in that it has a tensile strength of 90N or more, a tear strength of 80N or more, and a bending strength of 1.5N or more.

8. A method for manufacturing a vehicle fender liner according to any one of claims 1 to 4, comprising the steps of: A sheet-like substrate made of a fibrous body is formed by discharging fibers containing a core-sheath type composite fiber and a water-repellent fiber by an air-laying method, or by entangling the fibers by a fiber spreader or a fleece machine or a carding machine, and a sheet-like substrate made of a fibrous body is formed; One surface of the substrate is heated to 180°C to 240°C, and pressed and held at a predetermined thickness for 0.5 seconds to 30 seconds, to form a sheet having an average dynamic friction coefficient of 0.3 or less, a thickness of 0.05 mm to 2.0 mm, and a basis weight of 50 g / m on one surface of the substrate. 2 Up to 300 g / m 2 A high density film is formed. The substrate on which the produced film is formed is heated in a heating furnace at 120° C. to 240° C. for 10 seconds to 60 seconds, thereby making it easier to mold the substrate in the state in which the produced film is formed; The heated substrate is compressed and molded while being cooled in a press mold having a shape of a vehicle fender liner, so that the resulting film is placed on the tire side, and the resulting film has a total thickness including the resulting film of 1 mm to 15 mm and a basis weight of 400 g / m 2 ~1600g / m 2 A method for manufacturing a vehicle fender liner, comprising molding a vehicle fender liner comprising:

9. The method for manufacturing a vehicle fender liner according to claim 8, The predetermined thickness when one surface of the substrate is heated and compressed is 5 to 100 times the thickness before compression, and after the formation of the produced film, the thickness is restored to 1.0 to 0.6 times the thickness before compression; The manufacturing method for a vehicle fender liner is characterized in that the entire product is then heated and then compressed and molded while being cooled in a press mold having a shape of the vehicle fender liner to form the vehicle fender liner.

Citation Information

Patent Citations

  • Exterior material for vehicle, exterior article using the same, and forming method therefor

    JP2003112661A

  • Vehicle fender liner

    JP2011240821A